Respiratory pattern change in female and male runners by respiratory tract restriction using a respirator - Petr Bahenský; Tomáš Mrkvička; David Marko; Renata Malátová; Miroslav Krajcigr; Eric Harbour (PLoS ONE, 2026)
Respiratory protective equipment, particularly filtering facepiece respirators (FFRs), are increasingly used during physical activity, yet their influence on breathing mechanics remains unclear. This randomized, crossover trial investigated the impact of N95 FFRs on thoracoabdominal breathing patterns during graded treadmill exercise. Twenty competitive runners (10 male, 10 female; 18.9 ± 2.3 years) performed Bruce protocol tests with and without FFRs, while optoelectronic plethysmography quantified the contributions of pulmonary ribcage (RCp), abdominal ribcage (RCa), and abdomen (Ab) to tidal volume. Global ventilatory parameters (tidal volume, breathing frequency, minute ventilation) were unaffected by FFR use. However, compartmental analysis revealed significant alterations in breathing patterns at higher intensities. At 12 and 15 minutes, FFRs reduced RCp contribution (−7.85 ± 2.49%, P = 0.002; −8.41 ± 3.35%, P = 0.012) and increased Ab contribution (+5.97 ± 2.08%, P = 0.004; + 6.51 ± 2.80%, P = 0.020). Across all phases, females demonstrated moderate, but variable RCp dominance (P = 0.052). These findings indicate that while FFRs do not impair overall ventilation in trained runners, they substantially modify the biomechanics of breathing under load, reflecting compensatory adjustments that likely help preserve ventilatory efficiency. The results suggest that well-trained athletes may tolerate acute respiratory stress more effectively than the general population, which has implications for athletic training, rehabilitation, and occupational health where respirator use is required. Trial registration ClinicalTrials.gov NCT07032740